Pengaruh Entrepreneurial Marketing dan Kebijakan Pemerintah terhadap Daya Saing Kripik Tempe Sanan di Kota Malang - Novi Haryati (UPT Penerbitan Universitas Jember, 2018)
This study aims to identify the influence of Entrepreneurial Marketing andGovernment Policy on Competitiveness. Data analysis was carried out in quantitative descriptiveusing the concept of Entrepreneurial Marketing, while the second year, the research would beconducted using SEM-based WarPLS and SWOT to find out the relationship between importantfactors in developing the MSME market. The results of this study show that Tempe SananIndustrial Entrepreneurs have made 7 approaches in Entrepreneurial Marketing, namely:Proactiveness, focused Opportunity, Calculated risk taking, Innovativeness, Consumer Intensity,Value creation. Seven dimensions in Entrepreneur Marketing are intended to see continuitybetween important factors that need to be considered to produce optimal marketing.variablesEntrepreneurial marketing have a positive contribution to competitiveness while the governmentpolicy variable is not significant. Based on the weight diagram and rating of each element of theSWOT matrix, it can be seen that the position of the Sanan Tempe Chips Industry is in quadrantII. Despite facing various threats, the company still has internal strength. The strategy that mustbe applied in this condition is to use force to take advantage of long-term opportunities. Productdiversification strategies can overcome the problem of developing MSME Tempe Sanan Chips inorder to be able to compete in gaining market share of processed products in MEA 2025.